Overwhelmed by Routine Tasks: A Multi-Tasking Principle Agent Perspective - Dominique Demougin; Carsten Helm (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze a multitasking model with a verifiable routine task and a skill-dependent activity characterized by moral hazard. Contracts negotiated by firm/employee pairs follow from Nash bargaining. High- and low-skilled employees specialize, intermediate productivity employees perform both tasks. Compared to the efficient solution, more employees exert both tasks and effort in the routine task is inefficiently large. As work overload in the routine task is decoupled from a corresponding increase in remuneration, employees perceive a loss of control to allocate effort between the two tasks. Reductions in employees' bargaining power and improvements in monitoring technologies aggravate the issue.
Keywords: D82; D86; J41; M52; 330; multi-tasking; work overload; routine tasks; rent extraction; moral hazard; limited liability; Nash Bargaining